Industrial heritage in an era of climate catastrophe: Contamination as heritage - Thompson, Carolyn F. (Geographies of Post-Industrial Place, Memory, and Heritage, 2020)
The purpose of this chapter is to preliminarily explore the fruitfulness of understanding industrial heritage sites through the lens of environmental catastrophe in the 21st century. While geographers have been increasingly exploring heritage over the past few decades, concerned with its significance in terms of cultural and social representations, as well as an economic commodity, and industrial heritage has become more widely recognized as a key aspect of identity in the cities of the westernized world, research has overlooked the fascinating nexus between the industrial production marked in the sites of industrial heritage and the environmental outcomes of those processes. There is no concern more pressing in the present than the reality of climate change and environmental catastrophe and so this presentation considers exploring the interconnections between remembering the social and historical significance of industrial heritage sites and recognizing the ways these sites threaten our future. Through a preliminary case study of English Station, a disused power station on the Mill River in New Haven, Connecticut, I explore how this site represents the aspirations and progress of New Haven as an industrial, electrified, automobile city, as well as the current environmental catastrophes on our doorstep.
Keywords: dept.egm

Affordability, security, sustainability? Grassroots community energy visions from Liverpool, United Kingdom - Morrissey, J.; Schwaller, E.; Dickson, D.; Axon, S. (Energy Research & Social Science, 2020)
Envisioning societal futures for systemic low carbon transition is key to supporting the emergence of new configurations of the energy system. Such visions or ‘imaginaries’ facilitate wider societal support for system change. Given the urgency of the decarbonisation agenda, societal understandings of transitions processes and community ideas and visions about pathways for change assume a key role. The paper addresses an important gap in knowledge of place-based visions of energy system transition by soliciting views of community residents through a survey instrument, on what their perspectives on energy transition are. A case-study of Liverpool UK is presented, conducted as part of the EU Horizon 2020 ENTRUST project. Through a cluster analysis approach of study respondent perspectives, this study identities 4 distinct energy visions: (1) Community Affordability; (2) The Centre Ground; (3) Security First; and (4) Green Affordability. Identified visions present different perspectives on how energy is framed, with each vision characterised by distinct preferences on the extent to which stakeholder groups may influence the energy system as well as different views on the role of specific energy generation methods. Further, visions differ on the role of different actors and institutions in the energy transition. Identified energy visions provide insight into the ways in which grassroots communities consider how the energy system should transition in the coming years. The study contributes to understanding of spatially-situated and socially differentiated views of energy system transition, providing insight into contrasting viewpoints on current and future energy system priorities of residents of Liverpool, UK. © 2020 Elsevier Ltd
Keywords: Community; Energy visions; Energy-system; Grassroots; Low carbon transition; dept.egm; peer-reviewed

Contextualizing climate justice activism: Knowledge, emotions, motivations, and actions among climate strikers in six cities - Martiskainen, Mari; Axon, Stephen; Sovacool, Benjamin K.; Sareen, Siddharth; Del Rio, Dylan Furszyfer; Axon, Kayleigh (Global Environmental Change-Human and Policy Dimensions, 2020)
In August 2018, Swedish teenager Greta Thunberg started to strike from school on Fridays to protest against a lack of action on the climate crisis. Her actions sparked a historically large youth movement, leading to a series of school strikes across the world. Over the course of one week in September 2019, striking school children, students and other grassroots movements, such as Extinction Rebellion, called for everyone to participate in a global Climate Strike. This paper is based on comparative research with climate protesters in six cities: Brighton and London (United Kingdom), Montreal (Canada), New Haven and New York (USA), and Stavanger (Norway). Based on original interviews with 64 protesters, the study examines their knowledge, emotions, motivations, and actions in relation to climate change, including any lifestyle changes they have undertaken before or after their protests. Our findings show that protesters have varying degrees of knowledge about climate change, and have taken a range of actions in their own lives to address climate change. They also manifest a wide spectrum of emotions about climate change, and different motivations for taking part in climate strikes. These features are under-studied and dynamically evolving at the present conjuncture. On this basis, we call for expanded academic attention to human, emotional, epistemic, and seemingly mundane aspects of climate protests, their structural tendencies and relational expressions, and the implications for our ability to address underlying drivers. © 2020 Elsevier Ltd
Keywords: Brighton; Brighton and Hove; Canada; Climate protests; Climate strikes; Connecticut; England; Fridays for Future; Greta; Greta Thunberg; London; London [England]; Montreal; New Haven; New York; Norway; Quebec [Canada]; Rogaland; Social activism; Social movements; Stavanger; United Kingdom; United States; action plan; climate change; dept.egm; environmental justice; knowledge; lifestyle; peer; peer-reviewed; psychology

The socio-cultural dimensions of community-based sustainability: Implications for transformational change - Axon, Stephen (Journal of Cleaner Production, 2020)
There is substantial difficulty with effectively, and meaningfully, engaging the public with community-based sustainability projects as a method to facilitate sustainable lifestyles. Individuals engage with community projects in numerous ways: cognitively (knowledge), affectively (emotions), and behaviourally (actions). One prevalent consideration that individuals consider is other peoples’ (lack of) engagement; given that the success of community-based approaches addressing climate change is dependent upon the actions, and participation, of all local residents. Findings from focus groups in seven urban communities in the UK are presented that illustrate clear elements of ‘Othering’ as part of individual engagements with community-based sustainability projects. Primarily, there is substantial consideration towards what other people within the community know, feel, and do to engage with community-based projects. Residents distinguish themselves in opposition to those they view as engaging, and not engaging, in the same way as themselves and indicate the need for equitable participation amongst all residents. These considerations have the potential to project particular barriers on wider community engagement if left to develop, cause tension, and are not resolved. Implications for participatory strategies to meaningfully and effectively engage individuals with community-based sustainability and transformational change are outlined. Insights into how considerations of ‘Othering’ can be overcome so as not to cause negative engagements with other residents and attempts to live sustainably as part of a community approach are illustrated. © 2020
Keywords: Climate change; Communities; Community based approach; Community engagement; Community project; Community-based; Community-based projects; Local residents; Othering; Public engagement; Sustainability project; Sustainability science; Sustainable development; Sustainable lifestyles; Transformational change; Transformations; Urban community; dept.egm; peer-reviewed

Just energy transitions? Social inequities, vulnerabilities and unintended consequences - Axon, Stephen; Morrissey, John (Buildings and Cities, 2020)
Keywords: dept.egm; peer-reviewed

“I’m a bit of a waster”: Identifying the enablers of, and barriers to, sustainable food waste practices - Wakefield, Alysia; Axon, Stephen (Journal of Cleaner Production, 2020)
Food waste has become an area of increasing concern in recent years, since unsustainable food waste practices have been associated with a range of adverse environmental, economic and societal impacts. Food waste is a multi-sectoral issue and must be addressed as such, by ensuring policymakers, practitioners, and consumers are equipped with the relevant knowledge and understanding of the importance of sustainable food waste practices. By exploring current attitudes and understanding of this topic amongst consumers, a lack of education about the importance of this issue has been identified as a barrier to carrying out sustainable practices at the household level, along with excess packaging, cultural norms of overconsumption and inappropriate social marketing. In contrast, a number of enablers, including social pressures, access to appropriate facilities and encouragement from media advertisements appear to have been highly influential in infringing on the consciousness of consumers. Investigating these enablers and barriers has allowed a number of potential interventions to be identified, with the intention of addressing this issue using a multifaceted approach and encouraging society to carry out sustainable food waste practices in the future. © 2020
Keywords: Contrast media; Cultural norms; Economic and social effects; Food waste; Food waste management; Household level; Marketing; Multi-faceted approach; Policy makers; Social marketings; Social pressures; Societal impacts; Sustainable consumption; Sustainable development; Sustainable lifestyles; Sustainable practices; dept.egm; peer-reviewed